Factors Associated With Abnormal Initial 24-Hour Urine Studies in Pediatric Nephrolithiasis: Can We Better Select Patients for Evaluation? - Moyer, Andrea; Ellison, Jonathan S.; Medairos, Robert; Sheridan, Katherine R.; Paloian, Neil J. (Frontiers in Urology, 2022)
Abstract Background: Children, especially adolescents, constitute the most rapid growing demographic of nephrolithiasis. Due to the risks of recurrent stone disease, a 24-hour urine analysis is recommended for the evaluation of children at risk of recurrent nephrolithiasis or those who are otherwise interested in further evaluation. However, data regarding patients most likely to have abnormal urine studies are sparse. We aim to identify predictors of abnormal 24-hour urine studies in children presenting for evaluation of nephrolithiasis. Methods: A retrospective review of children < 17 years of age with a diagnosis of nephrolithiasis at both primary children’s hospitals within our state from 2012-2017 was performed. Children with an adequate initial 24-hour urine study (creatinine > 9 mg/kg/24 hours) not on a thiazide or potassium citrate during the study, were included. Factors associated with any abnormality (calcium > 4 mg/kg; oxalate > 45 mg/1.73 m2; citrate < 310 mg/1.73 m2[females] or < 365 mg/1.73 m2 [males]) were evaluated as well as magnesium, uric acid, volume, sodium, and phosphorous. Results: A total of 111 children were included, 69 of whom (62%) had at least one abnormal result. Of factors hypothesized to be associated with an abnormal 24-hour urine study, only sex was significant (p = 0.001). Males had a greater proportion of hypercalciuria (55%) and hypocitraturia (73%) and a slightly lower proportion of hyperoxaluria (48%) than females. Conclusion: Male sex was the only factor associated with an abnormal 24-hour urine study, largely driven by increased rates of hypercalciuria and hypocitraturia in males.